Influence of Radial Journal Profile of Main Bearing on Lubrication State - Chunjian Li; Junsheng Zhao; Guixiang Zhu; Xiuchun Li; Guodong Zhang (Jixie chuandong)
Taking the main bearing of a diesel engine as the study object， the lubrication state analysis model of the main bearing is established by taking the roughness and elastic deformation of the main bearing surface into account， and the influence of the radial profile of the main bearing on the lubrication state is analyzed. The results show that， compared with the calculated results without considering the radial journal profile， when the influence of the radial journal profile is taken into account， the minimum oil film thickness of the main bearing increases by 25.95%， the maximum oil film pressure decreases by 17.69%， the mean friction power loss decreases by 6.14% and the inclination of the spindle neck is improved. With the increase of journal roughness， the minimum oil film thickness increases， the maximum oil film pressure almost invariably， and the mean friction power loss increases.